2012
DOI: 10.1001/archgenpsychiatry.2011.1349
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Corticolimbic Interactions During Affective Processing in Children and Adolescents at Risk for Schizophrenia Revealed by Functional Magnetic Resonance Imaging and Dynamic Causal Modeling

Abstract: These results are the first demonstration of network analyses techniques for functional magnetic resonance imaging data in children and adolescents at risk for schizophrenia. Dysfunctional interactions within the emotional processing network provide evidence of latent vulnerabilities that may confer risk for disordered adolescent development and eventually the emergence of the manifest disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 89 publications
(105 reference statements)
3
70
0
Order By: Relevance
“…It nevertheless has proven to be more sensitive in identifying abnormal biological signatures in risk-groups, where activation analyses were not. For example, using DCM we recently documented disordered cortical–limbic endogenous connectivity and contextual modulation during an emotional appraisal task in children of schizophrenia parents (34). Notably, this finding emerged despite widespread overlap in activation networks across risk and control groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It nevertheless has proven to be more sensitive in identifying abnormal biological signatures in risk-groups, where activation analyses were not. For example, using DCM we recently documented disordered cortical–limbic endogenous connectivity and contextual modulation during an emotional appraisal task in children of schizophrenia parents (34). Notably, this finding emerged despite widespread overlap in activation networks across risk and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we used the variational Bayes method to estimate posterior probabilities of competing models. Bayesian parameter averages of coupling estimates (with a focus on modulatory coupling) were analyzed to determine potential differences in modulation as a function of attention and statistical significance was assessed using Bonferroni correction ( p  < 0.05)(32, 34). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, increased connectivity has been consistently found in risk variant carriers of the COMT and MIR137 genes [43,44], however this alteration has not been reported in patients or relatives. To date the only positive connectivity finding for emotion processing that has been identified in schizophrenia relatives is derived from a DCM analysis, where the authors revealed a decreased driving input to the visual cortex and an increased modulatory inhibition between the limbic cortex and the PFC, suggesting a potential DCM-based intermediate phenotype for schizophrenia [45 ]. This observation raises the possibility that different functional connectivity measures may not be equally suitable for the detection of intermediate phenotypes across different task domains.…”
Section: Emotion Processingmentioning
confidence: 99%
“…Effective connectivity is noted as the most parsimonious “circuit diagram” replicating the observed dynamic relationships between acquired biological signals (102). Recent evidence suggests reduced effective thalamocortical (54) and frontal–limbic (103) effective connectivity in genetic risk groups. These and other studies establish a pattern of general brain network dysfunction in adolescents at genetic risk for schizophrenia, suggesting that dysfunction in cortical networks is a plausible “end-point” in a cascade of genetic and neurodevelopmental events.…”
Section: Brain Network Dysfunction In the Adolescent Risk State For Smentioning
confidence: 99%